1998
DOI: 10.1046/j.1365-2125.1998.00670.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐linear fluvoxamine disposition

Abstract: AimsTo study the pharmacokinetics of fluvoxamine when given in increasing doses to healthy volunteers. Methods Ten healthy, non-smoking men were given maintenance treatment with fluvoxamine for 4 weeks. Eight subjects were CYP2D6 extensive metabolisers (EMs) and two were CYP2D6 poor metabolisers (PMs). As a measure of the CYP1A2 phenotype, the paraxanthine/caffeine ratio in saliva after intake of caffeine was studied. The fluvoxamine doses given were 25 mg day −1 the first week, 50 mg daythe second week, 100 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 25 publications
3
34
0
Order By: Relevance
“…Fluvoxamine average steady-state concentrations for each subject are shown in Table 4. These values are within the reported concentration ranges for these doses and consistent with the nonlinear disposition of this drug (Perucca et al, 1994b;Spigset et al, 1998). Fluvoxamine oral clearance decreased as the dose increased: oral clearances in the three phases were 94.7 Ϯ 78.7, 60.9 Ϯ 36.7, and 48.0 Ϯ 28.9 l/h, respectively.…”
Section: Fig 2 Inhibitory Effect Of Fluvoxamine On the Formation Ofsupporting
confidence: 68%
See 1 more Smart Citation
“…Fluvoxamine average steady-state concentrations for each subject are shown in Table 4. These values are within the reported concentration ranges for these doses and consistent with the nonlinear disposition of this drug (Perucca et al, 1994b;Spigset et al, 1998). Fluvoxamine oral clearance decreased as the dose increased: oral clearances in the three phases were 94.7 Ϯ 78.7, 60.9 Ϯ 36.7, and 48.0 Ϯ 28.9 l/h, respectively.…”
Section: Fig 2 Inhibitory Effect Of Fluvoxamine On the Formation Ofsupporting
confidence: 68%
“…The linearity and intercept values suggested that a good estimation of K i iv values can be obtained using only a single dose of inhibitor. Based on this observation, the results of a published study of fluvoxamine inhibition of the CYP2C19 catalyzed bioactivation of chloroguanide (Jeppesen et al, 1997) were used to calculate a K i iv of 25 nM (assuming that fluvoxamine plasma concentration at 100 mg/day is 199.3 nM; Spigset et al, 1998) and that only CYP2C19 catalyzes the formation of 4-chlorophenylbiguanide). This K i iv estimate is similar to the values obtained in the present study, which used a different probe of CYP2C19 and three doses of fluvoxamine.…”
Section: Fluvoxamine Inhibition Of Cyp2c19mentioning
confidence: 99%
“…Data are PHARMACOGENETICS, DRUG METABOLISM, AND CLINICAL PRACTICE conflicting regarding the effect of CYP2D6 on fluvoxamine concentrations, with a single-dose study reporting a 1.3-fold higher AUC in PMs , whereas in another no difference was observed (Christensen et al, 2002). Similar disparities were observed at steady state (Spigset et al, 1998;Christensen et al, 2002). Overall, the effect of the CYP2D6 genotype seems to be minor.…”
Section: Doxepin (Tertiary)/desmethyldoxepin (Secondary)mentioning
confidence: 51%
“…13,14 In the case of fluvoxamine, differences in concentration-time curves (AUCs) between CYP2D6 genotypes were described after single doses, 15,16 whereas multiple doses result in similar AUCs in PMs and in EMs indicating a strong inhibitory effect on CYP2D6 in EMs. 17 For fluoxetine undergoing enantioselective metabolism toward the S-enantiomer, impaired demethylation of Sfluoxetine in CYP2D6 PMs was observed. 18 However, since the metabolite desmethylfluoxetine is also an active antidepressant, no clinical implications should be expected with regard to variable metabolism of fluoxetine as the parent drug.…”
Section: Tricyclic Antidepressantsmentioning
confidence: 99%